Measuring Intellectual Capital: How to Manage Modified Value Wadded Intellectual Coefficient in Islamic Banking? - Hilmy Baroroh; Navisatul Muna; Nurhalyza Maulydha Pambudi (Sharia Economic and Management Business Journal (SEMBJ), 2025)
Background: This study aims to examine the impact of Intellectual Capital (M-VAIC) and its components Capital Employed Efficiency (CEE), Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE), and Relational Capital Efficiency (RCE) on firm value (Tobin’s Q), with profitability (ROA) serving as a moderating variable, in Islamic banking companies. Method: This study employs purposive sampling to select data samples, focusing on Islamic banking companies, including Bank Umum Syariah (BUS) and Unit Usaha Syariah (UUS), listed on the stock exchange during the period from 2019 to 2023. Data analysis is performed using Panel Data Regression and Moderating Regression Analysis with the aid of Stata 17. Results: The results indicate a significant effect of IC, SCE, and RCE on firm value, while CEE and HCE do not have a significant impact. Additionally, profitability significantly moderates the relationship between intellectual capital and firm value. Conclusion: The results show that the value of a bank in the eyes of the market is no longer solely determined by its physical assets or financial capital; instead, intangible strengths such as efficient internal systems, reliable technology (Structural Capital), and strong relationships with customers and communities (Relational Capital) are the main drivers of firm value. This study takes a modern and relevant approach by analyzing the most recent period (2019-2023) and specifically incorporating "Relational Capital" into its analysis.